Psicomotricidade e o idoso: buscando qualidade de vida na terceira idade através do lúdico - Vasconcelos, Maria Helena Lyra de (2016)
The following study comes to propose through the psychomotor means by which the use of playful comes to promote significantly the life of the elderly, promoting quality of life, and checking their contributions in order to offering new sources of studies. Before that, it was necessary the study through literature review, in order to observe the knowledge that exists on the subject, and the means by which the psychomotricity has been through the playful tool for the welfare for the elderly. Seeking the maximum possible sources, and basement in front of authors to gather information, where the greater aim is to understand the vision that exists on the playful, and his important role in third age; both preventively as Interventional form, using the knowledge that the psychomotor already offers. Therefore the objective of this research is to check the contributions to improvement in the life of the elderly, with specific goals to bring knowledge of the psychomotor concepts as well as their application; awareness of the elderly and its challenges, in addition to the meaning of playful and its possible tool to achieve this quality of life. Thus, realize on the results, the effectiveness that exists through the psychomotor activity, providing the playful quality of life that the elderly want, in order to enhance the psychomotricity as means of achieving through the playful, each and every stage of life, favoring always the welfare of the individual.